Every cloud has a silver lining: The experience of online learning in English language classes at Saudi universities in the post–COVID-19 era - Alqahtani, Muneer Hezam (Frontiers in Education, 2022)
This study investigates the perceptions of 149 English language students about online language learning at a state university in Saudi Arabia and how this experience has prepared them to continue online learning in post-pandemic times. It also investigates any differences in students’ attainment of the four language skills of reading, listening, writing, and speaking with respect to the online learning experience. Data were collected using a questionnaire with close-ended items with each item having an open-ended query. The findings of the study indicate that, overall, the students had positive attitudes toward learning English online whether during the pandemic or after it is over. However, their views differed regarding the acquisition of the four language skills; learning the receptive skills of reading and listening online was perceived positively, while learning the productive skills of writing and speaking online was perceived negatively as a result of the online learning mode. The study concludes that more advanced technical features are needed to be introduced onto online learning platforms for more effective learning outcomes and that the current platforms at universities fall somewhat short of the English language students’ needs.